Time-dependent Effects of Moderate- and High-intensity Exercises on Myocardial Transcriptomics - Li, Shunchang; Ma, Jiacheng; Pang, Xiaoli; Liang, Yu; Li, Xiaole; Wang, Manda; Yuan, Jinghan; Pan, Yanrong; Fu, Yu; Laher, Ismail (International Journal of Sports Medicine, 2022)
The heart is a highly adaptable organ that responds to changes in functional requirements due to exposure to internal and external stimuli. Physical exercise has unique stimulatory effects on the myocardium in both healthy individuals and those with health disorders, where the effects are primarily determined by the intensity and recovery time of exercise. We investigated the time-dependent effects of different exercise intensities on myocardial transcriptional expression in rats. Moderate intensity exercise induced more differentially expressed genes in the myocardium than high intensity exercise, while 16 differentially expressed genes were down-regulated by moderate intensity exercise but up-regulated by high intensity exercise at 12 h post- exercise. Both Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analysis indicated that moderate intensity exercise specifically regulated gene expression related to heart adaptation, energy metabolism, and oxidative stress, while high intensity exercise specifically regulated gene expression related to immunity, inflammation, and apoptosis. Moreover, there was increased expression of Tbx5, Casq1, Igsf1, and Ddah1 at all time points after moderate intensity exercise, while there was increased expression of Card9 at all time points after high intensity exercise. Our study provides a better understanding of the intensity dependent effects of physical exercise of the molecular mechanisms of cardiac adaptation to physical exercise.
Keywords: moderate-intensity exercise; high-intensity exercise; transcriptomics; differentially expressed genes; myocardium